Research on projection light field encoding and reconstruction based on parallel camera arrays - Feng Zhang; Xi Wang; Zhou Shi Shi; Chang Pei Ma; Xiao Yu Jiang (Scientific Reports)
Abstract This research introduces an advanced projection-based 3D light field reconstruction algorithm, specifically engineered to tackle the limitations of the conventional SPOC algorithm—namely its dependency on a symmetric (circular) framework and dense array image acquisition. The algorithm’s core innovation resides in the utilization of disparity images captured by parallel cameras: by selecting the two cameras with positions closest to the ideal configuration, it identifies pixels most similar to the object point through their captured imagery, thereby assigning pixel values to the projected image array. Furthermore, by integrating ray tracing principles, the algorithm enables sampling with a sparse camera array, facilitating high-fidelity 3D reconstruction. Experimental results, which compare computational efficiency and display performance against the SPOC algorithm, corroborate the efficacy and advantages of this approach.